Wear mechanism of flax/basalt fiber-reinforced eco friendly brake friction materials. (2nd January 2017) - Ilanko, Ashok Kumar; Vijayaraghavan, Srinivasan
Abstract: Fibre-reinforced polymer composites exhibit excellent mechanical and tribological properties. Due to these reasons, they are used in many engineering applications such as transmission and brake systems. In the present study, the wear mechanism of flax and basalt fibre-reinforced phenolic composites was studied using a pin-on-disc wear tester. The sliding conditions such as sliding velocity and normal force varied from 0.1 to 0.5 m/s and 9.81 to 49.04 N, respectively. The wear map of worn-out specimens were analysed using wear mechanism map developed using Fuzzy Clustering Method. Scanning Electron microscopy photographs were examined and wear map was correlated. Different wear mechanisms that dominated a particular wear regime were discussed in this paper.